Constituents of boesenbevgia sp. isolation and crystal structure of crotepoxide ([lr-(lα,2α,4α,5β,6α,7α)]-4-[(benzoyloxy)methyl]- 3,8-dioxatricyclo[5,1,0,02,4]octane-5,6-diyl diacetate) - Orasa Pancharoen (2018)
The crystal structure of crotepoxide, isolated from the rhizomes of Boesenbergia sp., has been determined by single crystal X-ray diffraction methods at 295 K, being refined to a residual of 0. 059 for 682 independent 'observed' reflections. Crystals are orthorhombic, P212121, a 23.53(2), b 10.59(1), c, 6.99(1) Å, Z 4. © 1984 ASEG.